Frequency of Borrelia burgdorferi sensu lato and Leptospira spp. in small rodents from Yucatan, Mexico - Dzib-Paredes, Gerardo; Rodríguez-Vivas, Roger Iván; Panti-May, Alonso; Noh-Pech, Henry; Rosado-Aguilar, José Alberto; Torres-Castro, Marco (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The spirochetes bacteria Borrelia burgdorferi sensu lato (s.l.) and Leptospira spp. cause Lyme borreliosis and leptospirosis, respectively, both zoonotic diseases of public health importance. In their respective epidemiological cycles, small rodents are accidental hosts and natural reservoirs of these bacteria. Small rodents in two the marginalized communities of Chan San Antonio and Sucopó located in the eastern zone Yucatán, Mexico were captured. Bladder, ear, and kidney samples were taken and used in the genomic deoxyribonucleic acid (DNA) extraction that was used for DNA search of B. burgdorferi s.l. and Leptospira spp. A total of 82 rodents of the species Mus musculus, Rattus rattus, and Heteromys gaumeri were captured. There was no evidence of B. burgdorferi s.l. DNA in the studied samples. Infection with Leptospira spp. was 1.21 % (1/82). The only positive individual belonged to the M. musculus species. It is concluded that, although the frequency of infection with Leptospira spp. was low and no evidence of DNA B. burgdorferi s.l. was found in the rodent studied population, their participation as accidental hosts or reservoirs in the respective transmission cycles of the genera bacteria evaluated cannot be discarded.